Solid-State Physics Introduction to the Theory - Patterson, James D. (Springer International Publishing, 2018)
This book teaches solid state physics in a comprehensive way, covering all areas. It begins with three broad topics: how and why atoms bind together to form solids, lattice vibrations and phonons, and electrons in solids. It then applies this knowledge to interactions, especially those between electrons and phonons, metals, the Fermi surface and alloys, semiconductors, magnetism, superconductivity, dielectrics and ferroelectrics, optical properties, defects, layered materials, quantum Hall effect, mesoscopics, nanophysics and soft condensed matter. Further important topics of the book are the evolution of BEC to BCS phenomena, conducting polymers, graphene, iron pnictide superconductors, light emitting diodes, N-V centers, nanomagnetism, negative index of refraction, optical lattices, phase transitions, phononics, photonics, plasmonics, quantum computing, solar cells, spin Hall effect and spintronics. In this 3rd edition, topics such as topological insulators, quantum computing, Bose-Einstein transitions, highly correlated electron systems and several others have been added. New material on magnetism in solids, as well as a discussion of semiconductors and a changed set of problems with solutions, are also included. The book also discusses "folk theorems" to remind readers of the essence of the physics without mathematics, and includes 90 mini-biographies of prominent solid state physicists of the past and present to put a human face on the subject. An extensive solutions manual rounds out the book.